Exon4 Amelogenin Transcripts in Enamel Biomineralization. (June 2015) - Stahl, J.; Nakano, Y.; Horst, J.; Zhu, L.; Le, M.; Zhang, Y.; Liu, H.; Li, W.; Den Besten, P.K.
Amelogenins are proteins formed by alternative splicing of the amelogenin gene, and are essential for tooth enamel formation. However, the unique functions of various alternatively spliced amelogenins in enamel formation are not well understood. In this study, we determined the spatiotemporal location of amelogenins derived from transcripts containing exon4 (AMG+4) in the enamel matrix, and the relative binding of recombinant AMG+4 to hydroxyapatite (HAP). Immunohistochemistry and mass spectrometry analyses showed that AMG+4 proteins were secreted into the enamel matrix at the early maturation stage. A stage-specific increase in the synthesis of AMG+4 was further supported by our observation that in mice overexpressing leucine-rich amelogenin peptide (TgLRAP), in which ameloblasts differentiate earlier, AMG+4 transcripts were also upregulated earlier. In vitro binding studies, supported by in silico modeling of protein binding to calcium and phosphate, showed that more recombinant AMG+4 bound to hydroxyapatite (HAP) as compared with recombinant AMG-4. The temporal and spatial localization of amelogenins containing exon4 peptide, and their functional differences in HAP binding, suggests that the unique properties of amelogenins containing exon4 cause a specific enhancement of biomineralization related to stabilization of early-formed HAP at the maturation stage.